Size-dependent antibacterial activity of copper nanoparticles against Xanthomonas oryzae pv. oryzae – A synthetic and mechanistic approach - Majumdar, Tapodhara Datta; Singh, Mukesh; Thapa, Mala; Dutta, Moumita; Mukherjee, Abhishek; Ghosh, Chandan Kumar (Colloid and interface science communications, 2019)
Xanthomonas oryzae pv. oryzae (X. oryzae), causing devastating bacterial leaf blight (BLB) disease in rice, is fast developing resistance against many available antibiotics, warranting an urgent need to develop an alternative control strategy. In this manuscript, we report copper nanoparticles (CuNPs) as an effective antibacterial agent against X. oryzae. We synthesized four different sized CuNPs in a narrow-size range (CuNP-1 – 18 nm, CuNP-2 – 24 nm, CuNP-3 – 28 nm and CuNP-4 – 33 nm) by chemical reduction method. The physicochemical characterizations of CuNPs were done by X-ray diffraction (XRD), dynamic light scattering (DLS), UV–Visible Spectroscopy (UV–Vis Spectroscopy) and transmission electron microscopy (TEM). The antibacterial activity of the CuNPs was found to be size and concentration dependent. Among all the CuNPs, CuNP-3 exerted the best antibacterial efficiency against X. oryzae due to the increased production of reactive oxygen radicals than the others. It also displayed increased activity compared to commercial antibiotic streptomycin sulphate. [Display omitted] •. Four different sized copper nanoparticles (CuNPs) viz CuNP-1, CuNP-2, CuNP-3 and CuNP-4 were synthesized from CuCl2.•CuNP-3 showed the best antibacterial activity against Xanthomonas oryzae pv. oryzae.•CuNPs produced reactive oxygen species causing lipid peroxidation, membrane disintegration and breakdown of genomic DNA.•CuNP-3 outperformed the commercial antibiotic streptomycin sulphate.